Fermentasi Ampas Tahu dan Limbah Sayuran Sebagai Media Pertumbuhan Cacing Sutra (Tubifex Sp.) Untuk Kebutuhan Pakan Ikan - Riska Agustina; Ervina Indrayani; Barnabas Barapadang (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Tubifex Sp. is an alternative feed for the growth of fish larvae and seeds. This study aims to determine the growth of Tubifex Sp. using fermentation media tofu pulp and vegetable waste. The research will be carried out from September to October 2020. Sample Tubifex Sp. taken at the Acai river, Jayapura City. Effective Microorganisms (EM-4) are used as a solution for the fermentation process. After 30 days, weighing is carried out to determine the growth of Tubifex Sp. The results showed that the growth of Tubifex Sp. on tofu pulp media (55.61 g) was higher than the vegetable waste media (46.7 g) and the control variable (35.5 g). There is a significant difference in the average growth of Tubifex Sp. on tofu dregs media with control variables. Otherwise, there is no significant difference between the growth rates of Tubifex Sp. on tofu dregs medium with vegetable waste, as well as between the average growth of Tubifex Sp. on vegetable waste media with control variables. Tofu pulp fermentation is better than vegetable waste as a substrate for the cultivation of Tubifex Sp. The availability of tofu pulp which is quite abundant and easy to obtain is highly recommended as a substrate fermentation medium for the growth of Tubifex Sp.Keywords: Tubifex Sp.; Fermentation; Tofu pulp; Vegetable waste; Fish feed